What it takes to get it right: A qualitative study exploring optimal handover of health programmes in Tonkolili District, Sierra Leone - Norman Sitali; Emily Briskin; Jonathan Foday; Caroline Walker; Kees Keus; Francis Smart; Engy Ali; Katherine Whitehouse (Taylor & Francis Group, 2023)
ABSTRACTSince 2015 Médecins Sans Frontières (MSF) has been supporting the Ministry of Health (MoH) in Tonkolili district, Sierra Leone, with an integrated health care approach at the community, primary health centre (PHC), and hospital level. This programme is planned to be handed over to MoH. To prepare for this handover, a qualitative study exploring elements of a successful handover was undertaken in 2019. Focus group discussions (FGD) with the community members (n-48) and in-depth interviews (IDI) with MSF staff, community leaders, and MoH staff in Sierra Leone (n-15) were conducted. Data were audio-recorded, transcribed verbatim from English, Creole, and Themne, coded, and thematically analysed. Participants expressed that an optimal project handover and exit strategy should be a continuous, long-term, the staggered process included from the inception of the programme design. It requires clear communication and relationship building by all relevant stakeholders and demands efficient resources and management capacity. Associated policy implications are applicable across humanitarian settings on the handover of programmes where the government is functional and willing to accept responsibilities.